EKSEKUSI SERTIFIKAT JAMINAN FIDUSIA PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 18/PUU-XVII/2019 - Muhammad Rutabuz Zaman (MIYAH : Jurnal Studi Islam, 2020)
Abstrak: This article aims to discuss the Fiduciary Guarantee after the Constitutional Court decision. So far, the meaning of the phrase "executorial power" and the phrase "the same as a court decision that has obtained permanent legal force", in article 15 paragraph (2) of Law Number 42 of 1999 concerning Fiduciary Guarantee, are interpreted differently and differ. First, it is interpreted as granting power / legitimacy to the fiduciary recipient (creditor) to directly execute the object of the fiduciary guarantee in the event that the fiduciary (debtor) has committed a breach of promise, so that the execution of the fiduciary guarantee certificate can be carried out immediately without going through a court. Second, the implementation of the execution of the fiduciary guarantee must still be carried out in accordance with the procedure and mechanism of execution as in the execution of court decisions that have permanent legal force (inkracht van gewidj). The Constitutional Court in its decision number 18 / PUU-XVII / 2019 states, Article 15 paragraph (2) UUJF, in particular the phrase "executorial power" and the phrase "the same as court decisions having permanent legal force" can only be said to be constitutional as long as it is interpreted that "to guarantee fiduciary, where there is no agreement on the occurrence of "default" (default) and the debtor objected to voluntarily hand over the object which is the fiduciary guarantee, then all legal mechanisms and procedures in the execution of the Fiduciary Guarantee Certificate must be carried out and apply the same as the execution of court decisions has permanent legal force.